PPI versus Placebo in the Treatment of LPR: A Meta‐analysis of Nine RCTs. (23rd August 2013) - Wineland, Andre M.; Piccirillo, Jay F.
Abstract : Objectives: Identify if proton pump inhibitors (PPIs) in the treatment of laryngopharyngeal Reflux (LPR) are superior to placebos. Study Design: Meta‐analysis of double‐blind randomized controlled trials (RCTs) of PPIs vs. placebo in adult participants with laryngeal symptoms and endoscopic findings of LPR. Methods: Articles were identified by searching MEDLINE, EMBASE, Scopus, and ClinicalTrials.gov without date limits. Relative risks were reported with 95% confidence intervals using a random‐effects model. Publication bias, heterogeneity, and sensitivity analysis were also conducted. Modified PRISMA guidelines were used to assess data quality. The primary outcome measure was defined as the proportion of patients with 50% reduction in self‐reported laryngeal symptoms. Results: Nine RCTs examining PPI vs. placebo (n = 402; 226 PPI/176 placebo) suggest PPI therapy is superior to placebo (relative risk [RR] 1.36; 95% confidence interval [CI] 1.02, 1.81; P = 0.036). Additional sensitivity analysis suggests PPIs provide a greater benefit for those < 50 years old or to those who receive therapy for > 8 weeks. Moderate heterogeneity was found (I2 = 41.1%, X2 = 13.57, d.f. = 8, P = 0.094) among the studies. Significant publication bias was detected through Egger's test (coefficient 2.06; 95% CI ‐0.41, 4.54; P = 0.09). Conclusions: PPI therapy appears to provide superior symptomatic relief for LPR when compared to placebo. Significant publication bias and pharmaceutical association was found among included studies. Future research should focus on identifying those patients who would benefit most from medical therapy.